Identification and Characterization of the Lysine-Rich Matrix Protein Family in Pinctada fucata: Indicative of Roles in Shell Formation - Jian Liang; Jun Xie; Jing Gao; Chao-Qun Xu; Yi Yan; Gan-Chu Jia; Liang Xiang; Li-Ping Xie; Rong-Qing Zhang (Marine Biotechnology, 2016)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Genome-wide analysis of Gro/Tup1 family corepressors and their responses to hormones and abiotic stresses in maize - Hongyou Li; Kaifeng Huang; Hanmei Du; Hongling Wang; Xin Chen; Shibin Gao; Hailan Liu; Moju Cao; Yanli Lu; Tingzhao Rong; Suzhi Zhang (Journal of Plant Biology, 2016)

Responses of soil inhabiting nitrogen-cycling microbial communities to wetland degradation on the Zoige Plateau, China - Li-sha Wu; Yuan-yang Nie; Zhi-rong Yang; Jie Zhang (Journal of Mountain Science, 2016)

Dynamic failure mode and energy-based identification method for a counter-bedding rock slope with weak intercalated layers - Gang Fan; Jian-jing Zhang; Xiao Fu; Li-rong Zhou (Journal of Mountain Science, 2016)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Amycolatopsis xuchangensis sp. nov. and Amycolatopsis jiguanensis sp. nov., isolated from soil - Jian-Rong Huang; Hong Ming; Shuai Li; Zhuo-Li Zhao; Xiao-Lin Meng; Jian-Xin Zhang; Zhong Tang; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2016)

Thioredoxins are involved in the activation of the PMK1 MAP kinase pathway during appressorium penetration and invasive growth in Magnaporthe oryzae - Shijie Zhang; Cong Jiang; Qiang Zhang; Linlu Qi; Chaohui Li; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary In Magnaporthe oryzae , the Mst11‐Mst7‐Pmk1 MAP kinase pathway is essential for appressorium formation and invasive growth. To determine their roles in Pmk1 activation and plant infection, we characterized the two thioredoxin genes, TRX1 and TRX2 , in M. oryzae . Whereas the Δ trx1 mutants had no detectable phenotypes, deletion of TRX2 caused pleiotropic defects in growth, conidiation, light sensing, responses to stresses and plant infection progresses. The Δ trx1 Δ trx2 double mutant had more severe defects than the Δ trx2 mutant and was non‐pathogenic in infection assays. The Δ trx2 and Δ trx1 Δ trx2 mutant rarely formed appressoria on hyphal tips and were defective in invasive growth after penetration. Pmk1 phosphorylation was barely detectable in the Δ trx2 and Δ trx1 Δ trx2 mutants. Deletion of TRX2 affected proper folding or intra‐/inter‐molecular interaction of Mst7 and expression of the dominant active MST7 allele partially rescued the defects of the Δ trx1 Δ trx2 mutant. Furthermore, Cys305 is important for Mst7 function and Trx2 directly interacts with Mst7 in co‐IP assays. Our data indicated that thioredoxins play important roles in intra‐cellular ROS signalling and pathogenesis in M. oryzae . As the predominant thioredoxin gene, TRX2 may regulate the activation of Pmk1 MAPK via its effects on Mst7.

Responses of arbuscular mycorrhizal symbionts to contrasting environments: field evidence along a Tibetan elevation gradient - Rong Yang; Shuming Li; Xiaobu Cai; Xiaolin Li; Peter Christie; Junling Zhang; Jingping Gai (Mycorrhiza, 2016)

PCI-24781 can improve in vitro and in vivo developmental capacity of pig somatic cell nuclear transfer embryos - Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Yu-Chen Zhang; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Xi-Jun Yin; Jin-Dan Kang (Biotechnology Letters, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

The Roles of Genes in the Neuronal Migration and Neurite Outgrowth Network in Developmental Dyslexia: Single- and Multiple-Risk Genetic Variants - Shanshan Shao; Rui Kong; Li Zou; Rong Zhong; Jiao Lou; Jie Zhou; Shengnan Guo; Jia Wang; Xiaohui Zhang; Jiajia Zhang; Ranran Song (Molecular Neurobiology, 2016)

Emerging role of adipokines in systemic lupus erythematosus - Hong-Miao Li; Tian-Ping Zhang; Rui-Xue Leng; Xiang-Pei Li; Xiao-Mei Li; Hai-Rong Liu; Dong-Qing Ye; Hai-Feng Pan (Immunologic Research, 2016)

G2 rotavirus within an emergent VP7 evolutionary lineage circulating in children with acute diarrhea in Guangxi Province of China, 2014 - Hui Jin Dong; Yuan Qian; You Zhang; Lin Qing Zhao; Ru Nan Zhu; Yi Nong; Zhao Jun Mo; Rong Cheng Li (Archives of Virology, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Heat shock protein 70 inhibits cardiomyocyte necroptosis through repressing autophagy in myocardial ischemia/reperfusion injury - Xiaojuan Liu; Chao Zhang; Chi Zhang; Jingjing Li; Wanwan Guo; Daliang Yan; Chen Yang; Jianhua Zhao; Tian Xia; Yuqing Wang; Rong Xu; Xiang Wu; et al. (In Vitro Cellular & Developmental Biology - Animal, 2016)

Chitooligosaccharide Inhibits Scar Formation and Enhances Functional Recovery in a Mouse Model of Sciatic Nerve Injury - Hongping Hou; Lihai Zhang; Zuguang Ye; Jianrong Li; Zijian Lian; Chao Chen; Rong He; Bo Peng; Qihua Xu; Guangping Zhang; Wenbiao Gan; Peifu Tang (Molecular Neurobiology, 2016)

Composition of phosphorus in wetland soils determined by SMT and solution 31P-NMR analyses - Wenqiang Zhang; Xin Jin; Yuekui Ding; Xiaolei Zhu; Nan Rong; Jie Li; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Phosphorus speciation of sediments from lakes of different tropic status in Eastern China - Wenqiang Zhang; Nan Rong; Xin Jin; Jie Li; Yuekui Ding; Xiaolei Zhu; Baoqing Shan (Environmental Science and Pollution Research, 2016)

Isolation and characterization of the marine algicidal bacterium Pseudoalteromonas S1 against the harmful alga Akashiwo sanguinea - Hong-Ye Sun; Yu Zhang; Hui-Rong Chen; Chang-Xing Hu; Hui Li; Zhang-Li Hu (Marine Biology, 2016)

The Inhibition Effect and Excessive Carbon Flux Resulting from Blocking Anthocyanin Biosynthesis Under Darkness in Begonia semperflorens - Kai Ming Zhang; Mei Li Guo; Dan He; Rong Hua Wu; Yong Hua Li (Journal of Plant Growth Regulation, 2016)

Population structure of Japanese Spanish mackerel Scomberomorus niphonius in the Bohai Sea, the Yellow Sea and the East China Sea: evidence from random forests based on otolith features - Chi Zhang; Zhenjiang Ye; Zengguang Li; Rong Wan; Yiping Ren; Shuozeng Dou (Fisheries Science, 2016)

Estimation of soil reinforcement by the roots of four post-dam prevailing grass species in the riparian zone of Three Gorges Reservoir, China - Rong-hua Zhong; Xiu-bin He; Yu-hai Bao; Qiang Tang; Jin-zhang Gao; Dan-dan Yan; Ming-feng Wang; Yu Li (Journal of Mountain Science, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Change of Polysaccharide Content and Its Relation with Nitrogen Level in Sugarcane Leaves Under Nitrogen-Fixing Bacteria Inoculation and Nitrogen Supply - Xi-Hui Liu; Hui-Ping Ou; Rong-Zhong Yang; Rong-Hua Zhang; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

Effect of long-term industrial waste effluent pollution on soil enzyme activities and bacterial community composition - Gangavarapu Subrahmanyam; Ju-Pei Shen; Yu-Rong Liu; Gattupalli Archana; Li-Mei Zhang (Environmental Monitoring and Assessment, 2016)

Effects of sialidase NEU1 siRNA on proliferation, apoptosis, and invasion in human ovarian cancer - Li-rong Ren; Li-ping Zhang; Shu-ying Huang; Yuan-fang Zhu; Wen-juan Li; Shan-yu Fang; Li Shen; Yan-ling Gao (Molecular and Cellular Biochemistry, 2016)

Rapid Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) by the Vitek MS Saramis system - Weiguang Shan; Jiaping Li; Ying Fang; Xuan Wang; Danxia Gu; Rong Zhang (Current Microbiology, 2016)